(untitled) (International Journal on Stereo & Immersive Media, 2025)
This article presents a research project exploring the unique potential of Stereoscopic 3D (S3D) cinema through experimental techniques that challenge traditional 2D filmmaking conventions. The research identifies two key areas for experimentation— frame shape and haptic vision—to demonstrate how S3D can offer immersive experiences that are not possible or are greatly diminished in 2D formats. This study investigates non rectangular screen shapes, such as ovals, and their effects on depth perception and emotional engagement. Additionally, it explores haptic vision, aiming to evoke tactile-like sensations through the manipulation of convergence, focus, and colour. The research culminates in the S3D film No Race, which incorporates Indigenous Australian-inspired contemporary dance to illustrate the narrative possibilities of these experimental methods. This article highlights S3D’s transformative potential for multi-sensory storytelling and challenges traditional 2D biases in cinematic production.